LEAST QUADRATIC NON-RESIDUE AND VINOGRADOV’S CONJECTURES - Abdunabiev, Jamshid (Educational Research in Universal Sciences, 2024)
Vinogradov’s conjectures are fundamental problems in number theory that have intrigued mathematicians for decades. One of the key aspects of these hypotheses is the concept of least square nonresidue, which plays a crucial role in understanding the distribution of prime numbers and the behavior of arithmetic functions. This article explores the meaning of least square non-residue in the context of the Vinogradov conjectures, shedding light on its significance for the study of prime numbers and deeper connections between number theory and algebraic structures. By delving into the complexities of these conjectures and their relationship to least square nonresidue, this abstract aims to provide a comprehensive overview of the current state of research in this fascinating area of ​​mathematics.